Outcomes following immunosuppressive therapy withdrawal after complete renal response in proliferative lupus nephritis - Javier Narváez; Francesca Mitjavila; Joan M Nolla; Paola Vidal-Montal; Montserrat Gomà; Xavier Fulladosa; Olga Capdevila; Joan Torras (Lupus Science and Medicine)
Objective To investigate the rate and factors influencing renal relapse (RR) in proliferative lupus nephritis (LN) patients who discontinued immunosuppressive therapy (IST), as well as the long-term renal outcomes following RR.Methods Retrospective, single-centre study of biopsy-confirmed LN patients who had received IST for at least 36 months and maintained complete renal response (CRR) for a minimum of 12 months before therapy discontinuation.Results Of a total of 106 patients meeting the inclusion criteria, 76 with proliferative classes were selected for analysis. The median duration of IST prior to discontinuation was 83.5 months (IQR 25th–75th: 53.5–120). Relapse occurred in 29 patients (38.2%) at a median of 26.5 months (IQR 25th–75th: 9.25–63.5 months) following IST withdrawal. Relapses were classified as severe in 9 cases (31%) and moderate in 16 cases (55.2%). Renal rebiopsy was performed in 25 of these patients (86.2%), with 80% retaining the same histological class.Discontinuation of IST at ≤34 years of age significantly increased the risk of RR (adjusted HR: 3.5). In contrast, an IST duration exceeding 48 months prior to discontinuation (HR: 0.26), maintaining CRR for at least 48 months (HR: 0.32), achieving complete remission per DORIS (definition of remission in systemic lupus erythematosus) criteria at IST withdrawal (HR: 0.21) and gradual IST tapering (HR: 0.09) were associated with a reduced risk of RR.Following reintroduction of IST, 20 out of 29 patients (68.9%) achieved CRR, 5 (17.2%) achieved a partial response and 4 (13.8%) did not respond; of these, 3 patients (10.3%) progressed to end-stage renal disease.Conclusions Successful withdrawal of IST is possible in carefully selected patients with proliferative LN. If an RR occurs, most patients are able to remain in remission after resuming IST.